THE INFLUENCE OF EMPLOYEE COMPETENCE, COMMITMENT AND PROMOTION ON WORK ACHIEVEMENT WITH MOTIVATION AS A MEDIATION VARIABLE - Firliana, Dania; Harahap, Pahlawansjah; Sujito, Sujito (IJOSMAS, 2023)
Certification is the most important component as proof that employees have expertise in their fields. This study aims to determine the factors that can improve the performance of the logistics function of the Central Java Regional Police. The independent variables in this study are Competence, Employee Commitment, and Promotion, and the dependent variable is work achievement with motivation as a mediating variable. This study uses quantitative methods by using questionnaires to collect the required data. The sample in this study was 82 employees of the Central Java Police logistics function. The analysis used is a structural equation model (SEM) analysis using the SmartPLS analysis tool. The results of this study indicate that competence and motivation have a significant effect on work achievement. The variables of Competence, Employee Commitment, and Promotion have an influence on work motivation. While the variable of Employee Commitment and Promotion has no effect on work achievement. As a mediating variable, motivation succeeded in mediating the effect of employee competence and promotion on employee achievement but not for commitment to employee achievement.